Вынужденное излучение активных сред красного диапазона спектра; Известия вузов. Физика; Т. 59, № 1 - Копылова Т. Н. Татьяна Николаевна; Гадиров Р. М. Руслан Мухамеджанович; Никонов С. Ю. Сергей Юрьевич; Валиев Р. Р. Рашид Ринатович; Тельминов Е. Н. Евгений Николаевич; Никонова Е. Н. Елена Николаевна; Солодова Т. А. Татьяна Александровна; Алексеева В. И. Вера Ивановна; Маринина Л. Е. Любовь Егоровна; Саввина Л. П. Любовь Прокофьевна (2016, 2016)
Заглавие с экрана